Breast oncology and the COVID-19 pandemic: Recommendations from the Brazilian Society of Clinical Oncology (SBOC) - Gilberto Luiz da Silva Amorim; Daniele Xavier Assad; Bruno Lemos Ferrari; Daniela Dornelles Rosa; Bruno Pacheco Pereira; Renan Orsati Clara; Clarissa Maria de Cerqueira Mathias (Brazilian Journal of Oncology, 2020)
The current pandemic moment of severe acute respiratory syndrome coronavirus 2 (SARSCoV-2) has completely changed health services, with most services being directed to the treatment of affected patients. Even during this critical period, cancer patients need to be treated, as delayed treatment can compromise the chances of a cure. The Brazilian Society of Clinical Oncology (SBOC) has developed recommendations to guide decisions in breast cancer treatment during the SARS-CoV-2 pandemic through their Breast Tumors Committee. Due to the scarcity of relevant data, discussions on systemic treatment and surgical decisions related to breast cancer biological sub- types, chemotherapy schemes, anti-HER2 therapy, adjuvant endocrine therapy, breast surgery, radiotherapy, follow-up and routine exams, long-term central venous catheters, bisphosphonate and denosumab, genetic counseling and metastatic disease were evaluated and recommendations were issued. For newly diagnosed breast cancer, if appropriate, start systemic treatment with neoadjuvant endocrine therapy or neoadjuvant chemotherapy (NACT) with anti-HER2 blockage if HER2 positive disease. Surgery should be promptly considered if disease progression during NACT, malignant phyllodes tumor or breast sarcoma. These recommendations should be adjusted according to the reality of each service (private or public) and according to the epidemiological issues COVID19 presents in each area and revised recommendations may arise at any time.